The STEM Glass Ceiling: The Influence of Immigration Status on STEM Trajectories of Afro-Caribbean Women (A Narrative Approach) - Rahming, Sophia Glenyse (Journal of International Students, 2021)
Afro-Caribbean women initially construct their science identity outside of the U.S. in unique sociocultural contexts where Black is dominant and British-styled instruction remains intact. Afro-Caribbean women often experience the “triple threat” minoritizing effects of being Black, female, and international/non-immigrant when they pursue STEM education and careers in the United States. Using grounded theory methods, I gathered the narratives of eight Afro-Caribbean women in STEM education or careers in the United States to examine how citizenship/immigration status influenced their STEM trajectories. Participants described how their educational and career aspirations were either supported or constrained by citizenship. Immigration status, therefore, operated as a figurative glass ceiling for some of the Afro- Caribbean women in this study limiting degree and career choice.